Assessment of growth and global developmental delay: a study among young children in a rural community of India - PGDMLE1, S M Dhaded2 MD, DM, S S Goudar3 MD, MHPE, Syed Sadat Ali MD, DHHM1*, Balaji PAMD (International Multidisciplinary Research Journal, 2011)
A cross-sectional study was done to assess the prevalence of growth and global developmental delay and the predisposing factors among children aged three years residing in rural communities of India. About 530 children at three years were assessed for growth and developmental delay. The Ages and Stages Questionnaire (ASQ) was administered to mothers by a trained interviewer. Growth measurements and hemoglobin estimation were done at the time of developmental evaluation. Socio-demographic characteristics of the families of children were ascertained. Prevalence of global developmental delay was estimated and association between development and maternal, child and household characteristics were explored. Physical growth was assessed by using WHO growth charts for weight for age, height for age and weight for height. Chi-square test was used to compare categorical variables. Differences were considered significant at P<0.05 level. The results showed that the prevalence of global developmental delay assessed by ASQ was 19.8%. Children displayed delay in personal-social (42.5%), gross motor (38.1.1%) and problem-solving skills (34.9%). Maternal educational level was positively associated with communication and problem-solving skills (P=0.000) while monthly household income was positively associated with communication, gross motor and problem-solving skills (p=0.000). The results suggest a high prevalence of developmental delay and poor child health in this rural population. Implementing early intervention programs may ameliorate the long term consequences of these developmental disorders.